Restenosis of Drug-Eluting Stents: A New Classification System Based on Disease Mechanism to Guide Treatment and State-of-the-Art Review. (August 2019) - Shlofmitz, Evan; Iantorno, Micaela; Waksman, Ron
Abstract : Despite on-going evolution and iteration of drug-eluting stent (DES) technology, the prevalence of in-stent restenosis (ISR) remains relatively unchanged, encompassing ≈10% of percutaneous coronary interventions. The mechanism of ISR is multifactorial, including biological, mechanical, patient, and operator-related factors. The main mechanical contributors are stent underexpansion or fracture, while biological factors include local inflammation leading to aggressive neointimal proliferation and late neoatherosclerosis. Intracoronary imaging is critical to identify the mechanism of ISR and tailor therapy accordingly. The presentation of DES-ISR is not benign and is challenging for optimal treatment. Among the proposed treatment modalities are scoring and high-pressure balloons, percutaneous coronary intervention with additional DES, atheroablative therapies by laser or mechanical atherectomy, drug-coated balloons, vascular brachytherapy, and surgical revascularization. We propose a new classification for ISR that differentiates among mechanical, biological, and mixed etiologies. Stratifying ISR by mechanism guides individualized treatment of DES-ISR to improve clinical outcomes. An algorithmic approach, guided by intracoronary imaging, for the treatment of DES-ISR, is recommended based on the specific cause of restenosis.